Construcción de la identidad suramericana a partir de la cooperación política en UNASUR. - Sánchez Gavi, Cintya Lorena. (2018)
The research proposes to analyze the identity associated with UNASUR as a legitimizing an element that acquires meaning through the influence of agents (political decisión - making countries within UNASUR and civil society). This analysis is approached from the constructivist perspective, through which the mutual agent - structure interaction is sustained; identity and interest within the framework of the structure at the UNASUR process The methodology used is discourse analysis . For this purpose, there were two State analysis units (Declarations of Heads of State) and civil society (Citizen Participation Forum) were analyzed.